2018
DOI: 10.1038/s41421-018-0011-8
|View full text |Cite
|
Sign up to set email alerts
|

Dual extra-retinal origins of microglia in the model of retinal microglia repopulation

Abstract: Elucidating the origin of microglia is crucial for understanding their functions and homeostasis. Previous study has indicated that Nestin-positive progenitor cells differentiate into microglia and replenish the brain after depleting most brain microglia. Microglia have also shown the capacity to repopulate the retina after eliminating all retinal microglia. However, the origin(s) of repopulated retinal microglia is/are unknown. In this study, we aim to investigate the origins of repopulated microglia in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
123
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(132 citation statements)
references
References 48 publications
9
123
0
Order By: Relevance
“…By contrast, two repopulating origins following microglial depletion in the retina have been described (Huang, Xu, Xiong, Qin, et al, ). One is the resident central‐emerging microglia in the optic nerve and the other is the extra‐retinal periphery‐emerging microglia from the ciliary body/iris (Huang, Xu, Xiong, Qin, et al, ). Two distinct resources including peripheral macrophages could also contribute to robust microglial regeneration independently of irradiation (Cronk et al, ).…”
Section: Microglial Repopulation Resolves Neuroinflammation: New Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, two repopulating origins following microglial depletion in the retina have been described (Huang, Xu, Xiong, Qin, et al, ). One is the resident central‐emerging microglia in the optic nerve and the other is the extra‐retinal periphery‐emerging microglia from the ciliary body/iris (Huang, Xu, Xiong, Qin, et al, ). Two distinct resources including peripheral macrophages could also contribute to robust microglial regeneration independently of irradiation (Cronk et al, ).…”
Section: Microglial Repopulation Resolves Neuroinflammation: New Cellmentioning
confidence: 99%
“…Additionally, embryonically seeded microglia and the newly repopulated cells may respond differently to environmental stimuli, as evidenced by two distinct cell types showing differential motilities in response to laser burn injury in vivo (Cronk et al, ). Using RNA sequencing it was determined that the gene profiles of fully repopulated microglia had been little influenced by administration of PLX5622 because no inflammatory related genes were up‐regulated or down‐regulated during depletion and repopulation processes (Huang, Xu, Xiong, Qin, et al, ). Consistent with this idea, Elmore and colleagues determined that repopulated microglia have relatively larger cell bodies than do resident microglia.…”
Section: Microglial Repopulation Resolves Neuroinflammation: New Cellmentioning
confidence: 99%
“…First, the residual microglia in the optic nerve repopulate the retina along the center‐to‐periphery axis, and second, macrophages from the ciliary body and iris relocate to the periphery and migrate toward the center. Furthermore, repopulated microglia fully restore the broad functionalities of naive microglia (Huang et al, ; Zhang et al, ). These repopulation mechanisms are mainly regulated by the neuronal chemokine CX3CL1 and its receptor (CX3CR1) in microglia (Zhang et al, ).…”
Section: Targeting Mononuclear Phagocytes In Retinal Degenerative Dismentioning
confidence: 99%
“…Rd1 and rd10 mice carry mutation in exon 7 and exon 13 of the beta subunit of the rod phosphodiesterase gene, respectively. (Huang et al, 2018a;Zhang et al, 2018). These repopulation mechanisms are mainly regulated by the neuronal chemokine CX3CL1 and its receptor (CX3CR1) in microglia (Zhang et al, 2018).…”
Section: Rd1 and Rd10mentioning
confidence: 99%
“…More recent studies have shown that newly-born microglia transiently express nestin early in repopulation; however, none of the repopulated microglia derive from nestin progenitors. Instead this static analysis of microglia in fixed tissue suggested that repopulated microglia are derived from the microglia that survive depletion in the cortex (<5%) rather than a specific progenitor population (Huang et al, 2018a;Huang et al, 2018b;. Similar to repopulation in the cortex, microglial repopulation in the retina was shown to be driven by remaining microglia; however, proliferation occurred in the central retina and these new microglia then migrated to repopulate peripheral areas, suggesting a specific site of microglial generation in the eye (Huang et al, 2018b;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 94%